Atlas of Ocular Optical Coherence Tomography - Hajizadeh, Fedra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a collection of optical coherence tomographic (OCT) images of various diseases of posterior and anterior segments. It covers the details and issues of diagnostic tests based on OCT findings which are crucial for ophthalmologists to understand in their clinical practice. Throughout the chapters all aspects of this non-invasive, popular imaging technique, known for ingenuity and accuracy, is clearly illustrated. Atlas of Ocular Optical Coherence Tomography, 2nd Edition has been fully revised to include updates optic disc disease and advancements in OCT for the diagnosis and monitoring of glaucoma. In addition, many other recent developments in CSCR, ARMD and OCT-A are highlighted throughout the book with new image modalities featured throughout. This book is an essential guide for general ophthalmologists and ophthalmology residences seeking an easy to use resource with numerous images and detailed descriptions of diseases. .
Introduction to Optical Coherence Tomography -- Age Related Macular Degeneration -- Diabetic Retinopathy and Retinal Vascular Diseases -- Central Serous Chorioretinopathy -- Epiretinal Membrane, Macular Hole and Vitreomacular Traction -- (VMT) Syndrome -- Optic Disc Anomaly, Glaucoma and other neuropathies -- Ocular Tumors -- Pathologic Myopia -- Hereditary Disease -- Uveitis and Intraocular Inflammation -- Anterior Segment Optical Coherence Tomography (AS-OCT).
Keywords: Ophthalmology; Radiology; Ophthalmology; Radiology; Eye Diseases -- diagnosis; Image Processing, Computer-Assisted; Tomography, Optical Coherence; Atlases